Pengaruh Customer Rating, Promosi Flash Sale, COD, dan Gratis Ongkir terhadap Keputusan Pembelian di Marketplace Shopee - Anna Zakiyah Hastriana; Anna Rara Bella Wildani (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2023)
Shopee Marketplace is here to help people fulfill their needs. By offering various features that attract consumers to decide on a purchase. Features used include ratings, flash sale promotions, cash on delivery and free shipping. This study aims to determine and examine the effect of Customer Rating, Flash Sale Promotion, Cash on Delivery and Free Shipping on Purchasing Decisions at Shopee Marketplace. This research is quantitative research with descriptive methods. The sample in this study amounted to 78 respondents using purposive sampling method. Data collection was carried out by distributing questionnaires (questionnaires) via Google form to 78 respondents. The data analysis method used is the classic assumption test and multiple linear regression analysis using SPSS 21. The results of this study indicate that the variables Customer Rating, Flash Sale Promotion, Cash on Delivery and Free Cream Cost have a positive and significant effect on purchasing decisions in the Shopee marketplace. This can be seen from the acquisition of the coefficient of determination test (R2) of 0.915 or 91.5%. Meanwhile, the partial test results also show that each independent variable has a positive and significant effect on purchasing decisions. This can be known from the results of the t test of the Customer Rating variable obtained a significance value of 0.000 ≤ 0.05 and a tcount value (13.011). The Flash Sale Promotion variable obtained a significance value of 0.020 ≤ 0.05 and a tcount value of (2.379). The Cash On Delivery variable obtained a significance value of 0.000 ≤ 0.05 and a tcount value of (4.717). The Free Shipping variable obtained a significance value of 0.002 ≤ 0.05 and a tcount value of (3.229).